Pendampingan Sertifikasi Halal UMKM Desa Pondokagung Kecamatan Kasembon Kabupaten Malang - Nadya, Alissa Qotrun; Hafidz, Ahmad ridho; Latifa, Aynul; Fikri, Shofil (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The purpose of this community service is to provide training, vocational assistance, promotion and management of MSME halal certification in Pondokagung Village, Kasembon Regency. The purpose of this analysis is to provide an understanding of the importance of registering a business and the benefits of a halal certificate for its business products. This community service activity consists of two objectives, namely assistance and socialization of the implementation of the Halal Assurance System and assistance in submitting halal certification documents to LPPOM MUI. After all the stages have been explained in the mentoring, it is continued with assistance for document input by handing over two MSMEs to one student on duty. The results of this activity are awareness of partner business units to implement a halal assurance system in their business and registration of business units in the halal certification process to LPPOM MUI Tujuan dari pengabdian masyarakat ini adalah untuk memberikan pelatihan, pendampingan vokasional, promosi dan pengelolaan sertifikasi halal UMKM di Desa Pondokagung Kabupaten Kasembon. Tujuan dilakukannya analisis ini adalah untuk memberikan pemahaman tentang pentingnya mendaftarkan suatu usaha dan manfaat sertifikat halal bagi produk usahanya. Kegiatan pengabdian kepada masyarakat ini terdiri dari dua tujuan yaitu pendampingan dan sosialisasi implementasi Sistem Jaminan Halal dan pendampingan penyerahan dokumen sertifikasi halal ke LPPOM MUI. Setelah semua tahap di jelaskan dalam pendampingan dilanjukan dengan pendampingan untuk input dokumen dengan menyerahkan dua UMKM kepada satu mahasiswa yang bertugas. Hasil dari kegiatan ini adalah kesadaran unit usaha mitra untuk menerapkan sistem jaminan halal dalam usahanya dan pendaftaran unit usaha dalam proses sertifikasi halal ke LPPOM MUI